F) (-5,5) * (-3 5/11)
G) -2 2/9 + 4,6
H) -1/2 * 2 1/4
I) -1,8 * (-5/6
J) (-6)² : (1+2³)
K)[(-3)² + 2³] * (-5)
Pomocy plis


Odpowiedź :

Odpowiedź:

F)

(-5,5) * (-3 5/11)  = -55/10 * (-38/11) = 5/5 * 19 = 19

G)

-2 2/9 + 4,6  = -2 2/9 + 4 3/5 = -2 10/45 + 4 27/45 = 2 17/45

H)

-1/2 * 2 1/4  = -1/2 * 9/4 = -9/8 = -1 1/8

I)

-1,8 * (-5/6 ) = -18/10 * (-5/6) = 3/2 = 1 1/2

J)

(-6)² : (1+2³)  = 36 : (1 + 8) = 36 : 9 = 4

K)

[(-3)² + 2³] * (-5)  = (9 + 8) * (-5) = -17 * 5 = -85

Szczegółowe wyjaśnienie: